Restraints and Opportunities of the Romanian Rural Areas - Surd, Vasile (Journal for Geography, 2010)
Although Romania disposes of an extremely valuable agricultural land, it has proved to be insufficient and irrationally exploited in the last two decades, as a direct consequence of the programme for returning the agricultural areas to the former individual landowners. The lack of technological agricultural means for cultivating the land, its excessive allotment, as well as the rather inappropriate involvement of the political factor in the decision making process and the invasion of imported agricultural products have generated a continuous process of degradation of the rural life as a whole and certain repercussions on the food safety. Currently, more than 50% of the Romanian agricultural area is not being cultivated, while the state imports more than 70% of alimentary products every year.
Keywords: urban-rural space; rural state; rural policy infrastructure; agricultural land; Romania